Severe syndromic ID and skewed X-inactivation in a girl with NAA10 dysfunction and a novel heterozygous de novo NAA10 p.(His16Pro) variant - a case report - Ingrid Bader; Nina McTiernan; Christine Darbakk; Eugen Boltshauser; Rasmus Ree; Sabine Ebner; Johannes A. Mayr; Thomas Arnesen (BMC, 2020)
Abstract Background NAA10 is the catalytic subunit of the major N-terminal acetyltransferase complex NatA which acetylates almost half the human proteome. Over the past decade, many NAA10 missense variants have been reported as causative of genetic disease in humans. Individuals harboring NAA10 variants often display variable degrees of intellectual disability (ID), developmental delay, and cardiac anomalies. Initially, carrier females appeared to be oligo- or asymptomatic with X-inactivation pattern skewed towards the wild type allele. However, recently it has been shown that NAA10 variants can cause syndromic or non-syndromic intellectual disability in females as well. The impact of specific NAA10 variants and the X-inactivation pattern on the individual phenotype in females remains to be elucidated. Case presentation Here we present a novel de novo NAA10 (NM_003491.3) c.[47A > C];[=] (p.[His16Pro];[=]) variant identified in a young female. The 10-year-old girl has severely delayed motor and language development, disturbed behavior with hyperactivity and restlessness, moderate dilatation of the ventricular system and extracerebral CSF spaces. Her blood leukocyte X-inactivation pattern was skewed (95/5) towards the maternally inherited X-chromosome. Our functional study indicates that NAA10 p.(H16P) impairs NatA complex formation and NatA catalytic activity, while monomeric NAA10 catalytic activity appears to be intact. Furthermore, cycloheximide experiments show that the NAA10 H16P variant does not affect the cellular stability of NAA10. Discussion and conclusions We demonstrate that NAA10 p.(His16Pro) causes a severe form of syndromic ID in a girl most likely through impaired NatA-mediated Nt-acetylation of cellular proteins. X-inactivation analyses showed a skewed X-inactivation pattern in DNA from blood of the patient with the maternally inherited allele being preferentially methylated/inactivated.